Occupational factors and the incidence of cancer of the bladder in Canada. Issue 6 (June 1988) - Risch, H A; Burch, J D; Miller, A B; Hill, G B; Steele, R; Howe, G R
Abstract : During 1979-82, a case-control study of occupational factors and urinary bladder cancer was conducted in Edmonton, Calgary, Toronto, and Kingston, Canada. A total of 826 histologically verified cases of cancer were individually matched by sex, age, and area of residence to 792 randomly selected population controls. Subjects were specifically asked about employment in several industries thought relevant to risk of bladder cancer. Information was also obtained on lifelong occupational history, with special attention given regarding exposures to fumes, dusts, smoke, and chemicals. In addition, subjects provided data on past medical and residential history, on intake of certain dietary items, and on exposure to tobacco and other lifestyle factors. Conditional logistic regression methods were used for the analysis. Under adjustment for cumulative lifetime cigarette consumption, it appeared that for both men and women, most of the occupational factors examined were not associated with significant alteration in risk of bladder cancer. For exposures during the period eight to 28 years before diagnosis, however, raised risk was suggested for men employed at least six months in the chemicals industry (odds ratio = 2.37, p = 0.004), in dye manufacturing or the dyeing of cloth (OR = 3.62 and 4.63, p = 0.041 and 0.035, respectively), as tailors (OR = 3.85, p = 0.015), or in jobs in which contact with diesel or traffic fumes occurred (OR = 1.69, p = 0.0008). Increased risk was also seen for men occupationally exposed to tars or asphalt (OR = 3.11, p = 0.019). This study then, at least for men, supports perhaps a few of the suspect industries as related to risk of bladder cancer.